HIWIND Observation of Summer Season Polar Cap Thermospheric Winds. Issue 11 (7th November 2019) - Wu, Qian; Knipp, Delores; Liu, Jing; Wang, Wenbin; Varney, Roger; Gillies, Robert; Erickson, Phil; Greffen, Michael; Reimer, Ashton; Häggström, Ingemar; Jee, Geonhwa; Kwak, Young‐Sil
Abstract: HIWIND (High altitude Interferometer WIND experiment) is a balloon‐borne Fabry Perot interferometer for daytime thermospheric wind observations. In this paper, we examine the summer polar cap thermospheric winds observed by HIWIND with the RISR‐C (Resolute Incoherent Scatter Radar‐Canada) observed ion drifts and electron densities. We also perform National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model simulations to compare with the HIWIND and RISR‐C observations. The standard Thermosphere Ionosphere Electrodynamics General Circulation Model underestimates the high‐latitude electron density and overestimates the thermospheric winds. The discrepancies between modeled and observed meridional winds are large near midnight and noon. After increasing the energy flux in the polar cap drizzle, the simulated electron density is comparable with the RISR‐C observations. However, large discrepancies with the HIWIND‐observed thermospheric winds persist. The cause of the model versus observation discrepancy in winds is probably due to the processes outside the polar cap. Key Points: HIWIND made first polar cap daytime thermospheric wind observation Normal TIEGCM underestimates the polar electron density and overestimates thermospheric winds HIWIND observed slightly equatorwind near the local noon